Implementation of Population Identification Numbers in the Social Security Program of Banten United in Serang City - Nufus, Nurhayati; Muhtar, Entang Adhy; Rusli, Budiman; Pancasilawan, Ramadhan (KnE Social Sciences, 2022)
Since the inception of the the Social Security program for the people in Banten United, this program has not been integrated with valid population data, or with DP3AKKB (Women’s Empowerment, Child Protection, Population and Family Planning, Population and Civil Registration Sector). The use of population identification numbers (NIK) should be maximized to harmonize the provision of social assistance through the Social Security program. Therefore, it is necessary to create a model for aligning NIK with the Social Security program, to ensure optimal efficiency and promote the strategic objectives of the program, namely improving social welfare through poverty reduction. NIK can be used to provide assistance directly in the form of money (in-cash transfers), as well as in the form of goods and services (in-kind transfers). NIK can also facilitate integrating economic and social policies in order to protect poor and vulnerable groups. An integrated social protection system covers social and economic vulnerabilities and their interactions, provides a comprehensive range of interventions based on measurable needs and contexts, and facilitates a multisectoral and coordinated approach to address multiple vulnerabilities and maximize their effectiveness and impact on multiple sectors. Currently, the basic problem in providing social assistance in Banten is that a systems approach and a multisectoral approach have not been developed. The systems approach is an effort to build and strengthen structures and mechanisms that facilitate the integration of a network of policy interventions to address a wide range of vulnerabilities. A multisectoral approach is to identify and maximize the relationship between social protection and its sectoral outcomes, such as education, health, nutrition, water and sanitation. Keywords: policy implementation, e-KTP, population identification number, the Social Security program for the people in Banten United